Laser-induced breakdown spectroscopy of aqueous silicone rubber in an argon environment - Deng, Yu; Peng, Bo; Hao, Yuguo; Du, Yijun; Zhou, Songsong; Gu, Chen; Zhou, Jun (Frontiers in Materials, 2022)
In a high humidity environment, the absorption of water in silicone rubber results in a significant decline or even loss in insulation performance, and the detection of the moisture content of silicone rubber is conducive to timely measuring the water absorption of silicone rubbers. Currently, the moisture content of silicone rubber can only be detected through manual sampling and laboratory analysis, which lack electric field analysis methods. Therefore, this paper proposes using laser-induced breakdown spectroscopy for the rapid qualitative and quantitative analysis of the moisture content of silicone rubber. Experiments were conducted on 50 silicone rubber samples with different moisture contents, with argon gas sprayed onto the sample surfaces to eliminate the interference of H and O elements in the air; a better argon gas flow rate of 3 L/min was determined. The information comprising the intensity and intensity ratio of the elemental spectral lines in the LIBS spectra of silicone rubber with moisture content was analyzed, with the results indicating that H elemental intensity increased as moisture content increased. Compared with the dry silicone rubber, the variation range of H/O and Al/H elements in the samples with different moisture contents was larger. Multivariate analysis was performed using a partial least squares regression model for the aqueous silicone rubber samples, and the model fit was obtained as 0.8088. The model prediction was better for the samples with moisture contents greater than 0.4%. The results indicated that the LIBS technique quantitatively analyzes the moisture content of silicone rubber, which is significant for improving the operation and maintenance of electric transmission lines.